IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DI KABUPATEN MAGELANG DI MASA PANDEMI COVID-19 (STUDI KASUS DI DESA KARANGREJO KECAMATAN BOROBUDUR) - Faza Salsabila Zannuba Rahmah; Dewi Rostyaningsih; , Hesti Lestari (Journal of Public Policy and Management Review, 2023)
The Covid-19 outbreak has affected the tourism sector and caused the closure of tourist attractions in Karangrejo Village. This causes the number of tourist visits to decrease, the PAD of Magelang Regency and people's income to decrease, some tourism actors lose their jobs, and tourist objects become less maintained because there are no tourist visits. This study aims to describe and analyze the implementation of tourism development policies in Karangrejo Village, as well as the supporting and inhibiting factors for the implementation of tourism development policies in Karangrejo Village during the Covid-19 pandemic. The method used is descriptive qualitative with data collection techniques using interviews, observation, and literature study. The implementation of tourism development policies in Karangrejo Village during the Covid-19 pandemic has been implemented correctly, although there are aspects that need to be reoptimized. The aspect that needs to be re-optimized is target accuracy. The aspects of policy accuracy, implementation accuracy, environmental accuracy, and process accuracy have been running optimally. The driving factors for implementation consist of policy standards and targets, implementing attitudes, and the social environment. The inhibiting factors for implementation are communication and resources. The advice that can be given is that actors need to socialize directly with the community, more massively and intensively. Actors can socialize through social media. Actors need to improve their capabilities and upgrade their skills and knowledge of tourism actors. This is done so that the services performed can be more professional with the Sapta Pesona program corridor.